Efektivitas Penggunaan Chewy Tool dalam Mengurangi Perilaku Menggigit Jari pada Murid dengan Gangguan Spektrum Autisme: Penelitian Single Subject Research - Tri Putri Anesa; Rahmahtrisilvia Rahmahtrisilvia; Mega Iswari; Endang Sri Handayani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Finger biting behavior in students with autism spectrum disorders is a stereotypical behavior that can hinder engagement in learning and pose a risk of self-injury. This study aims to determine changes in finger biting behavior through the use of chewy tools in students with autism spectrum disorders. This study used a quantitative approach with the Single Subject Research (SSR) method with an A-B-A design involving one subject. The study was conducted in three phases: an initial baseline phase (A₁) of three sessions without intervention, an intervention phase (B) of several sessions with the use of chewy tools, and a final baseline phase (A₂) of three sessions after the intervention was stopped. Data were collected through direct observation using an observation sheet for the duration of finger biting behavior during the learning process, then analyzed using visual analysis within and between conditions. The results showed a decrease in the frequency of finger biting behavior after the use of chewy tools, as indicated by a change in the direction of the trend from increasing/stable in the baseline phase to decreasing in the intervention phase as well as the ability to maintain behavioral changes in the final baseline phase. These findings suggest that chewy tools have the potential to be used as an intervention medium to help reduce finger biting behavior in students with autism spectrum disorders in the learning context.